Concepts, prevalence and characteristics of severe maternal morbidity and near miss in Brazil: a systematic review - Josy Maria de Pinho da Silva; Sandra Costa Fonseca; Marcos Augusto Bastos Dias; Aline Silva Izzo; Gabrielle Pires Teixeira; Pamela Pinto Belfort
Abstract Objectives: to analyze frequency, characteristics and causes of severe maternal morbidity (maternal near miss) in Brazil. Methods: a systematic review on quantitative studies about characteristics, causes, and associated factors on severe maternal morbidity (maternal near miss). The search was done through MEDLINE (maternal near miss or severe maternal morbidity and Brazil) and LILACS (maternal near miss, maternal morbidity). Data were extracted from methodological characteristics of the article, criteria for maternal morbidity and main results. Near miss ratios and indicators were described and estimated. Results: we identified 48 studies: 37 were on hospital based; six were based on health surveys and five were based on information systems. Different definitions were adopted. Maternal near miss ratio ranged from 2.4/1000 LB to 188.4/1000 LB, depending on the criteria and epidemiological scenario. The mortality rate for maternal near miss varied between 3.3% and 32.2%. Hypertensive diseases and hemorrhage were the most common morbidities, but indirect causes have been increasing. Flaws in the healthcare were associated to near miss and also sociodemographic factors (non-white skin color, adolescence/ age ≥ 35 years old, low schooling level). Conclusions: the frequency of maternal near miss in Brazil is high, with a profile of similar causes to maternal mortality. Inequities and delays in the healthcare were identified as association.